(untitled) (Journal of Universal Science Research, 2023)
Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathies, which occurs in 4–21% of women during reproductive age and is the most common form of hyperandrogenism [1, 2]. The clinical manifestations of PCOS are diverse, and most of them accompany a woman throughout her life, varying depending on age, ethnicity, constitutional and other factors. Due to the increase in average life expectancy, modern women spend quite a long period in peri- and postmenopause, which determines the need to monitor the clinical manifestations of PCOS, its long-term complications, as well as the features of the onset and course of age-associated diseases in this endocrinopathy [3–6].